Akkermansia muciniphila Ameliorates Clostridioides difficile Infection in Mice by Modulating the Intestinal Microbiome and Metabolites - Wu, Zhengjie; Xu, Qiaomai; Gu, Silan; Chen, Yunbo; Lv, Longxian; Zheng, Beiwen; Wang, Qiangqiang; Wang, Kaicen; Wang, Shuting; Xia, Jiafeng; Yang, Liya; Bian, Xiaoyuan; et al. (Frontiers in Microbiology, 2022)
Clostridioides difficile is a common cause of nosocomial infection. Antibiotic-induced dysbiosis in the intestinal microbiota is a core cause of C. difficile infection (CDI). Akkermansia muciniphila plays an active role in maintaining gastrointestinal balance and might offer the protective effects on CDI as probiotics. Here, we investigated the effects and mechanisms of A. muciniphila on CDI. C57BL/6 mice (n = 29) were administered A. muciniphila MucT (3×109 CFUs, 0.2 mL) or PBS by oral gavage for two weeks. Mice were pretreated with an antibiotic cocktail and subsequently challenged with the C. difficile strain VPI 10463. A. muciniphila treatment prevented weight loss in mice and reduced the histological injury of the colon. And it also alleviated inflammation and improved the barrier function of the intestine. The administration effects of A. muciniphila may be associated with an increase in short-chain fatty acid production and the maintenance of bile acids' steady-state. Our results provide evidence that adminsitration of A. muciniphila to CDI mice, with an imbalance in the microbial community structure, lead to a decrease in abundance of members of the Enterobacteriaceae and Enterocaccaceae. In short, A. muciniphila shows a potential anti-CDI role by modulating gut microbiota and the metabolome.